Air pollution and health outcomes: Evidence from Black Saturday Bushfires in Australia - Balasooriya, Namal N; Bandara, Jayatilleke S; Rohde, Nicholas (My University, 2022)
This paper presents new evidence of the causal effect of air pollution on Australian health outcomes, using the Black Saturday bushfires (BSB) in 2009 as a natural experiment. This event was one of the largest bushfires in Australian history and emitted approximately four million tonnes of CO2 into the atmosphere. We use data from the Household Income and Labour Dynamic Australia (HILDA) panel and compare the health status of individuals who were living in affected and unaffected regions before and after the event. Using a triple differences procedure, we further examine whether a difference in vulnerability to bushfire smoke exists comparing people living in urban or regional areas. We find that ambient air pollution had significant negative effects on health and that the magnitudes were actually larger for individuals residing in urban areas.
Social Science and Medicine
Keywords: Disadvantage, adversity and resilience; Health and wellbeing